calculando a expressão abaixo obtemos:
![Calculando A Expressão Abaixo Obtemos class=](https://pt-static.z-dn.net/files/dfe/cc1fec8c91f6ee8e040f23ab492aba4f.jpg)
Resposta:
Alternativa A.
Explicação passo-a-passo:
[tex]2 \: \times ( \frac{1}{2} - \frac{1}{3} ) \: \div \: ( \frac{1}{2} - \frac{1}{6} )^{2} = 2 \: \times ( \frac{3 \: - \: 2}{2 \: \times \: 3} ) \: \div \: ( \frac{6 \: - \: 2}{2 \: \times \: 6} )^{2} = 2 \: \times \: \frac{1}{6} \: \div \: (\frac{4}{12})^{2} = 2 \: \times \: \frac{1}{6} \: \div \: \frac{16}{144} = \frac{2}{6} \: \div \: \frac{16}{144} = \frac{2}{6} \: \times \: \frac{144}{16} = \frac{288}{96} \: \div \: 8 = \frac{36}{12} \: \div \: 12 = \: \frac{3}{1} = 3[/tex]